Committed to Integration: Local Media Representations of Refugee Integration Work in Northern Sweden - Ulrika Schmauch; Katarina Giritli Nygren (Nordic Journal of Migration Research, 2020)
The overall aim of this article is to explore the ways in which refugee reception and integration work is storied in the local newspapers of two rural municipalities in northern Sweden. Our results show that the strong emphasis on integration through employment present in national policy regimes is not readily visible in local media portrayals of integration. Instead, integration work is framed as a matter of commitment of individual refugees, volunteers and government administrative staff and, thus, as work with a high level of social support. We argue that the frame of commitment itself needs to be viewed in relation to the growing public support for limiting the resources available for this kind of work, as well as for the limitations for refugees to enter Sweden in the first place.